Kenali Pencetusnya, Taklukkan Serangannya, Pendidikan Kesehatan Mengenai Asma di SMAN 1 Padalarang - Theophylia Melisa Manumara; Putri Desriyanti; Nazwa Chusnul Amalya; Lydia Laura; Khoiriyatunnisa Khoiriyatunnisa; Andin Anggina Gustalia; Amanda Imara Putri Hapsari; Atikah Fauziyyah; Alvina Cantika; Nabila Safitri Novita (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Asthma is a chronic respiratory disease that commonly affects adolescents and can be triggered by various factors such as dust, pollution, cigarette smoke, and certain activities. Adolescents’ lack of knowledge about asthma triggers and prevention can increase the risk of respiratory health problems. This community service activity aims to improve students’ knowledge and awareness of asthma and its prevention. The activity was conducted at SMAN 1 Padalarang. The method used was an educational approach through the delivery of materials using PowerPoint, posters, leaflets, as well as pre-test and post-test evaluations using the interactive Kahoot platform. The materials covered included the definition of asthma, triggers, symptoms, complications, prevention, treatment, and the importance of maintaining respiratory health. The results of the activity showed an increase in students’ knowledge following the health education session. This was evident from the higher post-test scores compared to the pre-test scores, as well as the participants’ enthusiasm throughout the activity. It is hoped that this health education initiative will raise awareness among adolescents to adopt a healthy lifestyle and avoid risk factors that can trigger asthma.